Bone quality and muscle strength in female athletes with lower limb stress fractures - Schnackenburg, K. E.; MacDonald, H. M.; Ferber, R.; Wiley, J. P.; Boyd, S. K. (Medicine & Science in Sports & Exercise, 2011)
Purpose: Lower limb stress fractures (SF) have a high prevalence in female athletes of running-related sports. The purpose of this study was to investigate bone quality, including bone microarchitecture and strength, and muscle strength in athletes diagnosed with SF.